PUTUSAN HAKIM BERUPA PEMIDANAAN PERKARA TINDAK PIDANA PERBUATAN CABUL TERHADAP ANAK DIBAWAH UMUR - Anis Mohamad (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
This criminal morality of minors is not new, and this criminal act has obtained a place of regulation in the Criminal Code , which is set forth in the Second Book of Chapter XIV on "Crimes Against Adultery,” Research method in this writing is juridical-normative with approach of legislation, approach concept and approach case. The purpose of the study is to know the rules and regulations about obscene acts, and examine the legal aspects of the judge's decision to impose a criminal penalty of at least 3 years and a fine of at least Rp. 60.000.000, - so that no more violations of immorality will be committed in society. The result of the research can be concluded that the judge's decision in the form of criminal punishment of criminal act of obscene judge gives minimal punishment penalty and minimum penalty, because the proceeding of the session smoothly and lewd act is not until there is intercourse, hence the conviction of minimum and the most fine a little.